Defending Derrida: A Response to Milbank and Pickstock - Collins, Guy (Scottish journal of theology, 2001)
The reception of Jacques Derrida in the academic community has frequently been a source of controversy. Whilst America has often been hospitable to his thought, the situation in British and even French universities has occasionally been openly hostile. Derrida arouses an intensity of emotion illustrated by the two hundred and four academics at Cambridge University who attempted to block the award of an honorary degree in 1992. Like the reaction within other disciplines, the theological response was, and remains, fissured. Leading the critics, Brian Hebblethwaite lent vocal support to Derrida's detractors. Nevertheless, Hebblethwaite's published criticisms of Derrida at the time lack either theological or philosophical arguments. Instead, his assessment reveals a knowledge of Derrida gleaned almost exclusively from secondary sources, with the exception of a lone reference to Derrida's debate with John Searle in Limited Inc.